Endoscopic third ventricolustomy as treatment option for normal pressure hydrocephalus - Khalil Komlakh; Hamidreza Oveisi; Seyed Hossein Aghamiri (PAGEPress Publications, 2022)
This descriptive cross-sectional study was performed on 24 patients with normal pressure hydrocephalus who underwent endoscopic third ventriculostomy. The patients were selected by the available sampling method, and the data was collected through a researcher-made checklist. Data were analyzed using SPSS-26 software. Among 24 patients, 62.5% were male and the mean age was 70.85 ± 9.1 years. The results showed that there was no statistically significant relationship between age (p value = 0.43) and sex (p value = 0.37) with the success and failure rate of the surgical method. There was a significant difference between movement disorders (p value = 0.00) and dementia (p value = 0.00) before and after surgery, while there was no statistically significant difference between urinary disorders before and after surgery. (p value = 0.22). Endoscopic third ventriculostomy is an effective surgical method in the treatment of patients with normal pressure hydrocephalus and it improves the symptoms of movement disorder and dementia.